Health Status of Elderly People Living in Different Old Age Homes of Kathmandu - Bajracharya, Mijala; Dangol, Shikha (Journal of Manmohan Memorial Institute of Health Sciences, 2024)
Background: Old age can be broadly characterized by time- altered changes in an individual’s biological, psychological and health related capabilities and its implication for the consequent changes in the individual’s role in the economy and the society. The rising geriatric population is facing significant health problems in the developing world that are impacting the quality of their lives. The study aimed to assess health status of elderly people living in different oldage homes of Kathmandu and identify medications used by them. Method: A descriptive cross-sectional study was carried out in three old age homes of Kathmandu targeting the people aged 60 years and above. The data for the study was collected from the elderly people and health care professionals through face-to-face interview with structured questionnaire and reviewing medical records of residents of last one year. Results: Majority of residents were females (62.3%). The major part of the elderely population was in the age group of 71-80 years (50.9%). Regarding ethnicity, 34% were Brahmin followed by Newar and Chhetri (26.4% and 22.6%). 81.1% were illeterate and 50.9% were widow. The most common self reported health problem was pain and discomfort (88.7%).Regarding health, the most common diagnosed health problem was gastritis (69.8%) followed by hypertension (54.7%) and respiratory problems (30.1%). In general, female residents had more health problems compared to males. Pantoprazole was most commonly used medication (58.9%) followed by amlodipine (43.5%) and salbutamol sulphate (18.9%) . Medication compliance of elderly people was found to be good (87%).. Conclusion: This study revealed that gastritis was most common health problem and pantoprazole was most commonly used medication by elderly people living in old age homes of Kathmandu.